Pancasila dan Tujuan Pembangunan Berkelanjutan: Jalan Menuju Masyarakat Kosmopolitan - Claudia Syarifah (Universitas Diponegoro, 2019)
This paper reveals two important things: first, to show the relevance of the Pancasila with Sustainable Development Goals (SDGs) as a global norm which both are understood in this paper as embodiment of cosmopolitan values. Second, this case study reinforces the argument that the state remains important and its existence is not a barrier to the achievement of cosmopolitan values. In the middle of the debate over the durability and relevance of the state sovereignty, this paper shows that it is not barrier to cosmopolitanism – as is often argued by critics. Thus, at the level of international organization, the existence of cosmopolitan values are reinforced by state-level commitments to democracy.